Food Insecurity And Mental Health: Implication For Smallholder Rural Women Farmers In The Eastern Region Of Ghana - Azu, R.M. (University of Ghana, 2021)
The importance of food security and mental health have been duly recognized and highlighted by the SDGs as essentials to attaining development objectives. Studies have acknowledged the influence of food insecurity on mental health of vulnerable populations. However, there is a dearth of empirical data on this association amongst farmer populations. This study adds to the existing literature by examining the relationship between food insecurity and mental health on women farmers in the Eastern Region of Ghana. The study sourced data from the 2020 LinkINg Up: Women’s Agripreneurship Sustainability and Scale Up Initiative. The sample size was 165. The Food Insecurity Experience Scale (FIES) and the Self-Reporting Questionnaier-20 (SRQ-20) were used to measure food insecurity and mental health respectively. Social support was used as an intermediary variable. The study found out that, 45% of the women farmers were moderately or severely food insecure (FImod+sev). The prevalence of mental health distress among the respondents was reported to be 57%. The results also indicate that when controlling for all other variables, being moderately or severely food insecure is a significant predictor of mental health distress. Nonetheless, in this study, social support was not a predictor of mental health distress. Based on the findings, the study recommends promoting mental health and related issues as part of public health policy and service to rural poor farmers.
M.A. Population Studies
Keywords: food insecurity; mental health; social support; FIES; SRQ-20